Learning Methodologies for Learners with Dyslexia - Sehic, Sandro (International Journal of Educational Technology and Learning, 2017)
Dyslexia is a common reading disability that prevents many people from learning to read and sometimes completely disrupts all elements of the learning process if not addressed by educators. As a disability, dyslexia, cannot be cured; however, with proper teaching methods, it’s possible to significantly minimize the effects to allow students with dyslexia to successfully learn as well as those without dyslexia. The purpose of this article is to provide information about dyslexia and discuss some of the teaching methods educators can use to help learners with dyslexia overcome reading barriers and become successful learners.